PERAN SELF-EFFICACY TERHADAP BURNOUT PADA KARYAWAN YANG BEKERJA SECARA HYBRID - Firdauzy, Karunia Mulya (Polteknik Ilmu Pemasyarakatan, 2025)
The world of work has undergone a significant paradigm shift, especially after the COVID-19 pandemic. The hybrid work model, which combines remote work with in-office interactions, has been widely adopted by various organizations as a strategic adaptation. This study aims to determine the role of self-efficacy on burnout in employees working in a hybrid system. The research method used a quantitative approach with 160 respondents selected through an accidental sampling technique. The research instruments included the Burnout Scale, Self-Efficacy Scale, and Hybrid Working Scale. Data were analyzed using linear regression with the help of the JAMOVI program. The results showed that self-efficacy and hybrid work systems did not significantly influence burnout (p > 0.05), with an R² value of 0.00823, meaning that only 0.8% of the variation in burnout can be explained by these two variables. This finding suggests that other factors beyond self-efficacy and hybrid working have a greater influence on the emergence of burnout.